Clinical features and outcomes of elderly patients with antineutrophil cytoplasmic antibody-positive vasculitis: a single-center retrospective study - Hyo Jin Kim; Miyeun Han; Sang Heon Song; Eun Young Seong (The Korean Society of Nephrology, 2022)
Background We aimed to investigate the clinical characteristics and outcomes of patients aged ≥65 years with antineutrophil cytoplasmic autoantibody (ANCA)-positive ANCA-associated vasculitis (AAV) in Korea. Methods Seventy patients diagnosed with ANCA-positive AAV from 2006 to 2019 at a single center were analyzed and categorized into younger (aged <65 years) or elderly (aged ≥65 years) groups. Initial induction treatments were investigated according to age group. All-cause mortality and kidney outcomes were evaluated. Results After categorization by age, 34 (48.6%) and 36 patients (51.4%) were in the younger and elderly groups, respectively. In the elderly group, more patients were treated with oral cyclophosphamide (CYC) (30.6%) than with intravenous CYC (19.4%). During a median follow-up of 14.6 months (range, 3.0-53.1 months), 13 patients died (elderly group: 11 patients, 84.6%). In the elderly group, older age (hazard ratio [HR], 1.44; 95% confidence interval [CI], 1.09-1.90; p = 0.01), lower hemoglobin (HR, 0.21; 95% CI, 0.08-0.60; p = 0.003), and higher serum creatinine level (HR 14.17; 95% CI, 1.29-155.84; p = 0.03) were significant risk factors for all-cause mortality after adjustment. Oral CYC + steroid treatment was associated with decreased all-cause mortality compared to untreated induction immunosuppressants (HR, 0.01; 95% CI, 0.001-0.47; p = 0.02). Kidney failure or kidney recovery outcomes were not significantly different between the younger and elderly groups. Conclusion Patients aged ≥65 years had higher mortality rates than younger patients, and mortality was associated with older age, lower hemoglobin, higher serum creatinine level, and nontreatment compared to oral CYC + steroids.